Practice of data intellectual property reform: a case study of Zhejiang Province - HUANG Can; FAN Li; FAN Meiyan (大数据)
To accelerate the construction of the data intellectual property system, relevant theoretical research was reviewed and analyzed, and the experience of data intellectual property reform in Zhejiang Province was extracted as a case study. On the theoretical level, the academic community has conducted in-depth discussions on the concept of data, the confirmation of data rights, and the allocation of data rights, and emphasized the issues that the current data intellectual property registration system should pay attention to. On the practical level, as one of the first pilot regions for data intellectual property rights in China, Zhejiang Province takes “value creation and value realization” as its core, adheres to the principle of theory first and attaches great importance to in-depth research and careful planning; upholds the concept of system and promotes data intellectual property work in a larger working pattern, strengthens collaborative efforts and highlights ecological cultivation; adheres to the principle of putting demand first and promotes value realization. It has formed a unique pilot model of data intellectual property. Analyzing and summarizing the process and experience of data intellectual property reform in Zhejiang Province has certain reference significance for theoretical research focusing on the data intellectual property and the construction of the national data intellectual property system.